2012
DOI: 10.2166/wpt.2012.053
|View full text |Cite
|
Sign up to set email alerts
|

Field demonstration of bioaugmentation in trichloroethene-contaminated groundwater

Abstract: A pilot test was conducted to evaluate the effectiveness of bioaugmentation. Dechlorinating consortium in which the dominant microorganisms were Dehalococcoides species (DHC) possessing the vinyl chloride reductase gene (vcrA). The pilot test consisted of a direct injection system, including 2 injection wells. One injection well was for bioaugmentation, and the other, located approximately 20 m away, was for biostimulation. TCE was rapidly dechlorinated to cis-DCE in both wells. The first indication of reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…However, substantial dechlorination still occurred in MNA wells (although at a slower rate) suggesting that it would be a cheaper bioremediation approach, if accelerated contaminant removal was not needed. If no indigenous dechlorinating community was present, augmentation with dechlorinators (Dhc mixed consortia) would be standard practice [7,17,41].…”
Section: Reductive Dechlorination Of Tce To Ethenementioning
confidence: 99%
See 1 more Smart Citation
“…However, substantial dechlorination still occurred in MNA wells (although at a slower rate) suggesting that it would be a cheaper bioremediation approach, if accelerated contaminant removal was not needed. If no indigenous dechlorinating community was present, augmentation with dechlorinators (Dhc mixed consortia) would be standard practice [7,17,41].…”
Section: Reductive Dechlorination Of Tce To Ethenementioning
confidence: 99%
“…For example, Okutsu et al showed that the addition of "bioaugmentation agents contributed to shortening the clean-up time better than biostimulation by increasing the initial Dehalococcoides sp. (Dhc) population in the groundwater" in a pilot study of TCE contaminated groundwater [7]. Chemical compounds (biostimulation) can also be added to contaminated samples to stimulate the biological degradation of the pollutants [8].…”
Section: Introductionmentioning
confidence: 99%